Immunomodulatory biomaterials for vascularized and innervated skeletal muscle repair - Mottel, Lauren G.; Shields, Brennagh R.; Kwee, Brian J. (Frontiers in Immunology, 2025)
The repair of functional innervated and vascularized skeletal muscle from severe injuries, such as critical limb ischemia, denervation, and volumetric muscle loss, remains a critical clinical challenge. Regenerative cell therapies are often hindered by donor site morbidities and rapid clearance from injured tissue. Furthermore, emerging tissue engineering and biomaterials approaches are often stifled by–and may even worsen–the chronic, inflammatory microenvironment that debilitates these sites of muscle injury, as well as the underlying peripheral nerves and microvessels. Consequently, the role of the immune system in tissue repair has been increasingly studied and capitalized upon in the design of regenerative biomaterials to overcome these challenges. In this review, recent strategies for the development of immunomodulatory biomaterials for vascularized and innervated skeletal muscle repair will be discussed within the context of muscle, nervous, and vascular tissues, as well as the respective roles of immune cells and tissue progenitors during these repair processes. These strategies span chemical functionalization, sustained presentation of immunomodulatory cues, and inflammatory responses to natural and synthetic biomaterials, among other approaches.